2000
DOI: 10.1001/archneur.57.7.956
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Therapy in Myophosphorylase Deficiency (McArdle Disease)

Abstract: This is the first controlled study indicating that creatine supplementation improves skeletal muscle function in McArdle disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 34 publications
4
80
0
3
Order By: Relevance
“…Although sustained muscle performance and exercise tolerance of animals with muscle creatine depletion are quite good, there are deficits in muscle performance at the onset of intense contractions (1,16,35). Furthermore, functional deficits in some patients with muscle inflammatory myopathy, dystrophy/congenital myopathy, and other neuromuscular diseases (43) are exacerbated by the reduction in muscle PCr concentration, as oral creatine supplementation improves performance in many cases (42,44,45). Thus PCr and, by inference, total creatine (Cr total ϭ PCr ϩ Cr) are essential for optimal function of mammalian skeletal muscle.…”
mentioning
confidence: 99%
“…Although sustained muscle performance and exercise tolerance of animals with muscle creatine depletion are quite good, there are deficits in muscle performance at the onset of intense contractions (1,16,35). Furthermore, functional deficits in some patients with muscle inflammatory myopathy, dystrophy/congenital myopathy, and other neuromuscular diseases (43) are exacerbated by the reduction in muscle PCr concentration, as oral creatine supplementation improves performance in many cases (42,44,45). Thus PCr and, by inference, total creatine (Cr total ϭ PCr ϩ Cr) are essential for optimal function of mammalian skeletal muscle.…”
mentioning
confidence: 99%
“…However, in patients with McArdle disease, oral creatine supplementation in both high (150 mg/kg daily) and low (60 mg/kg daily) doses did not result in elevated PCr/ATP levels. 6,7 With low-dose creatine, working capacity for ischemic exercise improved, and we found a higher consumption of PCr during aerobic and ischemic low-level exercise in patients with McArdle disease. However, high-dose creatine cannot be recommended because it worsened clinical symptoms of exercise intolerance; patients reported an increase in both the number of pain episodes and the myalgia pain score.…”
Section: Creatine Treatmentmentioning
confidence: 69%
“…Recent positive trials have been reported for patients with muscular dystrophy [6], inflammatory myopathies [2] and McArdle [5] disease, whereas no effect on muscle strength could be found in patients with hereditary neuropathies [9]. In mitochondrial cytopathies, the effect of Cr supplementation was inconsistent [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…In mitochondrial cytopathies, a consistent effect of Cr could not be demonstrated [3,4]. In different types of muscular dystrophies and in McArdle disease, a mild beneficial effect of Cr supplementation was recently shown [5,6]. The present study was designed to evaluate therapeutic efficacy and side effects of Cr in DM1 patients.…”
Section: Introductionmentioning
confidence: 96%